2010
DOI: 10.1097/bot.0b013e3181b8b036
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Quantitative Ultrasound of the Calcaneus With Dual-Energy X-ray Absorptiometry in Hospitalized Orthopaedic Trauma Patients

Abstract: Substantial logistical difficulties are inherent in attempting to obtain DXA scans in orthopaedic trauma patients at our regional trauma center. For those patients who did undergo DXA, a strong predictive relationship was seen between hip bone mineral density and QUS parameters. QUS thresholds in defining low- and high-risk subjects for osteoporosis in this population using this device are proposed. QUS is a simple, reliable, and relatively inexpensive tool for evaluating osteoporosis risk in orthopaedic traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In the population of postmenopausal women investigated in this study, a significant correlation was found between each DXA site and the QUS parameters. Consistent with other studies among older women, the correlations between the QUS T score and DXA T score at the hip and femoral neck were better than those for the lumbar spine T scores …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the population of postmenopausal women investigated in this study, a significant correlation was found between each DXA site and the QUS parameters. Consistent with other studies among older women, the correlations between the QUS T score and DXA T score at the hip and femoral neck were better than those for the lumbar spine T scores …”
Section: Discussionsupporting
confidence: 90%
“…Consistent with other studies among older women, the correlations between the QUS T score and DXA T score at the hip and femoral neck were better than those for the lumbar spine T scores. 17,19 The ability of calcaneal QUS to identify women with a DXA T score of -2.5 or lower at the right hip (AUC, 0.887) excelled in comparison to a T score of -2.5 or lower at the lumbar spine (AUC, 0.704) or left femoral neck (AUC, 0.824). Additionally, noteworthy was the very strong AUC of 0.956 for measurements of the right calcaneus and right hip in patients between 50 and 65 years, which would indicate an especially high potential use of this device for the prescreening of hip fractures in women of this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the reliability of calcaneal QUS in assessing low BMD. 14,15,16,17,18 In our study, OSTA index did not correlate with BMD (T-score) when the entire sample was analyzed. However, on subgroup analysis based upon age, OSTA index significantly correlated positively with BMD in women in the age group of 50-55 years.…”
Section: Discussionmentioning
confidence: 81%
“…These data speak to the importance of continued efforts in patient education and the need for more proactive referrals to specialists in nutrition and obesity management. Much like the emerging role of the orthopaedic surgeon in the early management of osteoporosis and metabolic bone disorders in postfracture care in older populations [13,[16][17][18], we believe SCFE presents a unique and perhaps the most important opportunity for the orthopaedic surgeon to be proactive in education and clinical intervention regarding obesity, which can greatly improve the prognosis for SCFE as well as the overall health of the pediatric patient. We also suggest that prophylactic pinning might be considered for morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%